Negara Versus Pasar : Mendiskusikan (Kembali) Arah Kebijakan Politik Ekonomi Indonesia - Husnul Atiyah (Institut Kewarganegaraan Indonesia, 2025)
The direction of Indonesia’s economic policy is often a subject of debate among experts. This is partly because various economic policies are often inconsistent. On one hand, there is a tendency for the state to side with the people. However, in other policies, the state tends to favor the market. Indonesia is often said to have adopted a Pancasila economy. Some also refer to it as a people’s economy. However, in practice, the difference between the two is not very clear. Often, these labels merely become political commodities. This article aims to discuss this issue further by examining the policies adopted by the government, especially in the final years of President Jokowi’s administration, namely the issuance of the Government Regulation in Lieu of Act (Perpu) No. 2 of 2022 On Job Creation (Perppu Cipta Kerja) and the Bauxite Ore Export Ban in 2023. These two policies have elicited a range of reactions, with the first policy being considered too favorable to the market and corporations, while simultaneously causing significant harm to workers. In contrast, the second policy has received many positive responses, even from those who criticized the first policy. Using a literature review method, this article finds that Indonesia’s political economy policies tend not to be based on ideological considerations, but rather on strategic and practical economic calculations and, consequently, are often inconsistent with the ideology they promote.